Occurrence of Catharus fuscescens, veery (Passeriformes: Turdidae), in the south of the state of Minas Gerais, addendum on its wintering area in ecotono Brazil - Moura, Aloysio Souza de; Lasmar, Dunia; Machado, Felipe Santana; Moura, Guilherme Wince de; Barros, Dalmo Arantes de; Fontes, Marco Aurélio Leite (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2025)
The veery, Catharus fuscescens, is a migratory bird and a northern visitor that includes Brazil in its route. Although the south of the state of Minas Gerais is ornithologically well studied, the species had not previously been recorded in the region. This record was obtained during mammals studies using camera traps in the municipality of Lavras, MG, represents the first documented occurrence of Catharus fuscescens in the ornithological literature for this area and highlights its implications for understanding the species’ wintering area in Brazil.
Keywords: New registration; Bird; South of Minas Gerais